2022
DOI: 10.3390/cancers14010224
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 3T MRI in Women with IB1 Cervical Cancer in Determining the Necessity of Less Invasive Surgery

Abstract: Purpose: Cervical cancer that is invisible on magnetic resonance imaging (MRI) may suggest lower tumor burden than physical examination. Recently, 3 tesla (3T) MRI has been widely used prior to surgery because of its higher resolution than 1.5T MRI. The aim was to retrospectively evaluate the utility of 3T MRI in women with early cervical cancer in determining the necessity of less invasive surgery. Materials and methods: Between January 2010 and December 2015, a total of 342 women with FIGO stage IB1 cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Cervical cancer that is not visible on MRI strongly suggests a lower tumor volume compared to those that are visible on MRI (1)(2)(3). Therefore, tumor invasion of the parametrium or vagina is extremely rare in invisible cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer that is not visible on MRI strongly suggests a lower tumor volume compared to those that are visible on MRI (1)(2)(3). Therefore, tumor invasion of the parametrium or vagina is extremely rare in invisible cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported studies showed that postoperative outcomes were good when Federation of Gynecology and Obstetrics (FIGO) stage IB1 cervical cancer was not visible on preoperative magnetic resonance imaging (MRI) (1)(2)(3). This cancer has a much lower tumor burden than those visible on MRI.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that patients with a non-visible tumor had more favorable characteristics in terms of histological features and oncological outcomes compared with patients with visible tumors, suggesting how preoperative imaging may guide surgical radicality. Interestingly, they reported a significant difference in the number of squamous cell carcinomas (SCCs) versus non-SCCs between the two groups that, on the one hand, may have affected the oncological outcomes, but on the other hand, may suggest different MRI characteristics according to the histological type [ 3 ].…”
mentioning
confidence: 99%